Fedir Schmidt. Impressions of a prisoner of war (Part ІІ) - Domanovska, Maryna; Kurushyna, Maryna (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2025)
Relevance of the publication of the source. The text is the second and final part of the translation from Russian stories by Fedir Schmit (1877–1837) about his staying in German captivity, published in the Kharkiv newspaper “Yuzhny Kray” in January 1915. The famous Byzantine scholar, archaeologist, museum expert, and dean of the Faculty of History and Philology of Kharkiv University Fedir Schmit immediately after his return from Germany presents his memoirs, which are an important source of personal origin. It also complements the biography of the scientist with interesting details and observations. The emotional and chaotic presentation fully corresponds to the position of a patrial of the Russian Empire regarding the assessments of the causes and the beginning of the Great War, however, the scientist sincerely thanks his German colleagues for temporary shelter, the opportunity to continue his scientific studies, and the promotion of his exchange for a German officer. Fedir Schmit’s memoir publications until recently remained unnoticed by researchers. Therefore, their translation into Ukrainian makes an important source on the history of the First World War and Kharkiv University available to the public.